Childhood leukemia a practical handbook - Reaman, Gregory H.; Smith, Franklin O.; SpringerLink (Online service). (Heidelberg Springer, 2011)
This book is a comprehensive and up-to-date compendium on all aspects of childhood acute lymphoblastic and acute myeloid leukemia, which together constitute the most frequent cancer in the pediatric age group. After introductory chapters on the epidemiology and biology of pediatric leukemia, treatment considerations are extensively reviewed, with emphasis on the use of risk-adjusted treatment approaches. Promising targeted agents are discussed, and strategies for the development of new agents are appraised. The late effects of leukemia and its therapy are then considered in depth, with due attention to management of the psychosocial impact of the disease. Finally, global strategies to improve leukemia care and outcome are reviewed, and future directions discussed. The authors are internationally recognized experts and offer a largely evidence-based consensus on etiology, biology, and treatment. This handbook has far-reaching applicability to the clinical diagnosis and management of pediatric leukemia and will prove invaluable to specialists, generalists, and trainees alike.
Part 1. Genetics and the Epidemiology of Leukemia in Children -- Epidemiology of Acute Childhood Leukemia -- Part 2. Biology of Pediatric Leukemia -- The Biology of Acute Lymphoblastic Leukemia -- Biology of Acute Myeloid Leukemia -- Part 3. Treatment Considerations in Childhood Leukemia -- Classification and Treatment of Acute Lymphoblastic Leukemia -- Treatment of Acute Myeloid Leukemia -- Part 4. The Impact of Pharmacogenetics and Pharmacogenomics of Childhood Leukemia -- Pharmacogenetic and Pharmacogenomic Considerations in the Biology and Treatment of Childhood Leukemia -- Part 5. The Potential Role of Biologically Targeted Therapy for Childhood Leukemia -- Promising Targeted Agents -- Strategies for New Agent Development and Clinical Trial Considerations -- Part 6. Late Effects of Leukemia and Its Therapy -- Late Sequelae in Children with Acute Lymphoblastic Leukemia: Impact on Long-Term Survival and Quality of Life -- Acute Toxicities, Late Sequelae, and Quality of Survivorship in Children with Acute Myeloid Leukemia: The Impact of Allogeneic Stem Cell Transplant -- Part 7. Psychosocial Implications of Acute Leukemia Diagnosis and Treatment for Children and Families -- Appreciation and the Interdisciplinary Management of the Psychosocial Impact of Leukemia on Children and Their Families -- Part 8. Global Strategies to Improve Leukemia Care and Outcome for Children -- Improved Outcome for Children with Acute Leukemia: How to Address Global Disparities -- Part 9. Perspectives and Future Direction -- Future Challenges and Opportunities to Improve Outcomes for Children with Leukemia.
Electronic reproduction.
Keywords: Leukemia in children -- Handbooks, manuals, etc; Leukemia, Myeloid, Acute; Precursor cell lymphoblastic leukemia-lymphoma.; Child; Treatment outcome; Medicine; Electronic books